Kto uratuje Ariadnę? — palingeneza kreteńskiego mitu w popfeministycznych retellingach (na przykładzie „Pani labiryntu” Magdy Knedler i „Ariadny” Jennifer Saint) - Głos, Mikołaj (Zagadnienia Rodzajów Literackich, 2023)
The aim of this article is to analyze popfeminist retellings of known mythical stories. For the purposes of this text, two of the most popular novels on the publishing market have been selected at present — Jennifer Saint’s Ariadne and Magda Knedler’s Pani Labiryntu. Before analyzing the above novels, the most important theoretical findings regarding the presence of myth in contemporary, recent literature and pop culture will be recalled. A fundamental issue that needs to be addressed will be the objection of some researchers who claimed that myth is degenerating in popular literature. The findings of feminist criticism, whose research¬ers still emphasize the lack of female mythology, will also be important, as well as the fact that contemporary writers attempt to restore female genealogy in their works by reinterpreting stories embedded in culture, such as the myth of Theseus, etc. The analysis of the mentioned novels will be carried out on two levels: I will look at how the authors create women in Ari¬adne’s immediate surroundings, as well as men. This procedure will be aimed at answering the question posed in the title — who will save Ariadne? The result of the aforementioned analysis will be the thesis that contemporary retellings still reproduce stereotypical issues regarding patriarchal narratives despite the creation of pseudo-feminist heroines who, lost in the issues of the nature of identity and belonging, cannot fully free themselves from the power of violent men and make the same mistakes.